Nature's architect - Bong, Joseph Choon Fah; King, Patricia Jie Hung (Universiti Putra Malaysia Press, 2013)
In the forest or in an oil palm station, we sometimes see soil mounds that could be up to 1 meter tall. These are termite mounds. The common termite species that is a mound builder is the Macrotermes gilvus Hagen. The mound is actually a sort of 'house' that contains numerous living 'quarters' or lamellae which are interconnected by an intricate network of tunnels for instant and efficient communication and accessibility, or escape.